Effect of Systemic Pesticide Phosphamidon on Haematological Aspects of Common Frog Rana tigrina - Sounderraj, S.F. Lesley (International Journal of Pharmaceutical & Biological Archive, 2012)
ABSTRACT The impact of phosphamidon toxicity on biochemical aspects of blood cells and nucleus size of RBC of Rana tigrina resulted in a significant decreased in protein level were as increased in carbohydrate and lipid level. Cell and nucleus size of RBC also exhibited a decreasing trend